The relationship between crisis response strategies and behavioral intentions: a systematic literature review - Jiang, Xiaoyu; Kamarudin, Syafila; Cai, Yingying; Miao, Pu; Huang, Wenhong (Review of Communication Research, 2024)
Crisis response strategy is a pivotal concept for organizations in crisis communication, serving as a valuable framework for examining public behavioral intentions. Few systematic reviews have examined the impact of crisis response strategies on organizations. This paper aims to investigate the relationship between crisis response strategies and behavioral intentions within organizations. Adhering to PRISMA guidelines, this systematic literature review involved a comprehensive analysis of the Scopus and Web of Science databases, yielding 33 relevant studies. These studies, which utilized crisis response strategies as independent, moderating, or mediating variables, were classified into different research domains, including business and management, and communication. Analysis of the literature identified sixteen main themes of crisis response strategies: (1) accommodation related, (2)bolstering, (3)coping strategies, (4)corporate social responsibility(CSR), (5) corrective action, (6)courtesy, (7)defensive, (8)denial, (9)diminish, (10) evasion of responsibility-related, (11) information strategy, (12)intimidation,(13)rebuild strategies-related, (14) reduction of offensiveness-related, (15) speed, and (16) sympathy, encompassing 28sub- themes. Quantitative and qualitative analyses provided substantial empirical support for a significant relationship between crisis response strategies and behavioral intentions, including supportive behaviors, purchase intentions, secondary crisis communication, and word of mouth. The paper concludes with a presentation of the results and suggestions for future research directions and organizations.